Persepsi Guru Pamong terhadap Kompetensi Profesional Mahasiswa Praktik Lapangan Kependidikan di SMK - Fikla Yulia Darma; Ahyanuardi Ahyanuardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
Professional competence is one the must be possessed by a teacher. This research aims to determine the perceptions of supervisor teachers on the professional competence of PLK students at SMK Negeri 2 Lubuk Basung. This type of research is descriptive. With a research population of ninety-three teachers in the academic year 2019/2020. The sample used is only twenty-eight majoring teachers. Data were collected using a questionnaire with of question items was thirty-three. Using a Likert scale for the answer scoring system. Based on the research result, it can be concluded that; supervisor teachers perceptions of PLK students related to indicators of understanding learning material by seventy-seven point three percent in the medium category; while the indicators for sorting learning material are eighty point four percent in a good category; for indicators of organizing learning material by seventy-four point zero percent with the medium category; for the indicator to empower learning resources by eighty point two percent with the good category, for indicators od choosing and determining learning material by seventy-three point eight percent with the medium category.